Evaluating the Impact of Chemical Complexity and Horizontal Resolution on Tropospheric Ozone Over the Conterminous US With a Global Variable Resolution Chemistry Model. (22nd June 2022) - Schwantes, Rebecca H.; Lacey, Forrest G.; Tilmes, Simone; Emmons, Louisa K.; Lauritzen, Peter H.; Walters, Stacy; Callaghan, Patrick; Zarzycki, Colin M.; Barth, Mary C.; Jo, Duseong S.; Bacmeister, Julio T.; Neale, Richard B.; et al.
Abstract: A new configuration of the Community Earth System Model (CESM)/Community Atmosphere Model with full chemistry (CAM‐chem) supporting the capability of horizontal mesh refinement through the use of the spectral element (SE) dynamical core is developed and called CESM/CAM‐chem‐SE. Horizontal mesh refinement in CESM/CAM‐chem‐SE is unique and novel in that pollutants such as ozone are accurately represented at human exposure relevant scales while also directly including global feedbacks. CESM/CAM‐chem‐SE with mesh refinement down to ∼14 km over the conterminous US (CONUS) is the beginning of the Multi‐Scale Infrastructure for Chemistry and Aerosols (MUSICAv0). Here, MUSICAv0 is evaluated and used to better understand how horizontal resolution and chemical complexity impact ozone and ozone precursors over CONUS as compared to measurements from five aircraft campaigns, which occurred in 2013. This field campaign analysis demonstrates the importance of using finer horizontal resolution to accurately simulate ozone precursors such as nitrogen oxides and carbon monoxide. In general, the impact of using more complex chemistry on ozone and other oxidation products is more pronounced when using finer horizontal resolution where a larger number of chemical regimes are resolved. Large model biases for ozone near the surface remain in the Southeast US as compared to the aircraft observations even with updated chemistry and finer horizontal resolution. This suggests a need for adding the capability of replacing sections of global emission inventories with regional inventories, increasing the vertical resolution in the planetary boundary layer, and reducing model biases in meteorological variables such as temperature and clouds. Plain Language Summary: A new configuration of the Community Earth System Model (CESM)/Community Atmosphere Model with full chemistry (CAM‐chem) supporting the capability of horizontal mesh refinement is developed. This configuration is the beginning of the Multi‐Scale Infrastructure for Chemistry and Aerosols, which will create a unified infrastructure to model atmospheric chemistry and aerosols across scales in the Earth system. The capability in CESM/CAM‐chem to use grids with horizontal mesh refinement is a novel advancement because the regional and global model components are seamlessly connected such that there is consistency in the physical and chemical processes between the components, which increases accuracy in prediction and efficiency in model development. This work evaluates this new model configuration over the conterminous US against measurements from five aircraft campaigns, which occurred during 2013. By evaluating model results against observations not only for ozone, but also ozone precursors, photolysis rate constants, temperature, planetary boundary layer height, etc., model skill at representing processes important for ozone formation and loss is inferred. Updates to horizontal resolution and chemistry improve simulated ozone and ozone precursors as compared to observations, but biases remain. The physical and chemical processes that are missing or erroneous in the model are highlighted to help prioritize future work. Key Points: A new configuration of the Community Atmosphere Model with full chemistry supporting horizontal mesh refinement is developed This configuration is the beginning of the Multi‐Scale Infrastructure for Chemistry and Aerosols Updating chemistry and horizontal resolution improves simulated ozone and ozone precursors compared to aircraft observations